Priority and appropriateness of upper endoscopy out-patient referrals: Two-period comparison in an open-access unit. Issue 11 (November 2019) - Meggio, Alberto; Mariotti, Giuliano; Gentilini, Maria; de Pretis, Giovanni
Abstract: Background: In the early 2000s we introduced a prioritization model for referrals based on involvement of primary care physicians (PCPs) and specialists. Aims: Assess the application of that model of prioritisation, comparing gastroscopies performed 8 years apart, with respect to priority level, appropriateness and relevant endoscopic findings (REFs). Methods: The studies included 247 and 354 out-patients, who had undergone gastroscopy in 2006 and in 2014, respectively. To reduce interspecialists variability, both studies were performed by the same specialist as investigator. Results: In both years, most patients were assigned low-priority referral by PCPs (78.6% and 75.1% respectively). The agreement PCPs versus specialist on referral priority was moderate in 2006 (0.60, Landis–Koch scale 0.41–0.60) and high in 2014 (0.81, Landis–Koch scale 0.81–1.00). In both years we observed a similar rate of inappropriateness: 27.5% and 27.1%, respectively. Due to multiple logistic regression, the odds ratio (OR) for REF increased when: (i) very high-priority referral versus nopriority referral was indicated (8.813 OR, p = 0.0012), (ii) referral followed the guidelines (9.29 OR, p<0.0001), and (iii) agreement of priority occurred (1.911 OR, p = 0.0308). Conclusions: Our findings highlighted that the issues of low-priority referrals should be addressed in order to discontinue gastroscopy overusing and reduce related operational costs.